Screw cleaning material, preparation method thereof and screw cleaning method of processing equipment
By combining modified inorganic filler with matrix resin, combined with surfactant and other ingredients, the existing screw cleaning materials are easily agglomerated, uneven dispersed, insufficient cleaning force and easy damage to the screw, achieving efficient, environmentally friendly and non-damaging the screw.
Patent Information
- Application Number
- CN202411839218.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing screw cleaning materials are prone to clumping, uneven dispersion, insufficient cleaning force and easy damage to the screw.
Modified inorganic fillers are used to modify alcohol compounds and silane coupling agents to improve the dispersion of inorganic fillers and the binding force with the matrix resin, and combine the combination of surfactants, compatible agents and antioxidants to form a screw cleaning material with environmental protection, strong cleaning ability and no damage to the screw.
It realizes efficient and thorough cleaning of the screw surface, avoids screw damage, and reduces the amount and time-consuming of cleaning materials.
Smart Images

Figure CN119613862A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite polymer materials, and in particular to a screw cleaning material and a preparation method thereof, and a screw cleaning method for processing equipment. Background Art
[0002] During the processing of plastic products, processing equipment such as extruders will have more or less raw materials accumulated, which will cause waste of raw materials and environmental pollution during color change and material change operations. For example, the residue of pigment in the screw will cause significant color deviation and cause product failure. Therefore, the cleaning of these processing equipment is very important, and professional cleaning agents need to be used to completely remove the residues through the cleaning process to ensure the normal operation and production efficiency of the extruder.
[0003] CN106978277A discloses a method for preparing calcium carbonate for screw cleaning agent. The calcium carbonate used is light calcium coated on the surface of heavy calcium, and then the surface is modified with a modifier. The modification requires the addition of a crystal control agent, a pH adjuster, ethylene bisstearamide, polyethylene glycol, lauryl alcohol ether phosphate, diethylene glycol butyl ether, ethyl acetate, etc., and the system temperature and pH value must be strictly controlled in the middle. Although the amount of cleaning material is saved, the modification steps are cumbersome and the preparation is difficult.
[0004] CN102618401A discloses a twin-screw high-efficiency and environmentally friendly granulation particle cleaning agent and a production method thereof. The main components are 10-30 parts of base resin, 60-80 parts of inorganic powder, 0-10 parts of lubricant, and 0-10 parts of coupling agent. The cleaning purpose is achieved by mechanically rubbing a large amount of inorganic powder against the screw, and the cleaning efficiency is low.
[0005] CN105924931A discloses a method for preparing an efficient plastic screw cleaning agent. However, a large amount of glass fiber is added therein. During use, the mechanical friction between the filler and the screw will accelerate the damage to the screw. In addition, these fillers have poor fluidity and poor compatibility with the resin, and serious self-residue will occur without the effect of shear force at the die head.
[0006] CN106674723A discloses a plastic extruder or injection molding machine screw cleaning agent, which is used to clean the barrel and screw of the extruder or injection molding machine. The cleaning agent is composed of the following ingredients: 25%-40% of hard cleaning agent glass fiber, 5%-10% of interface cleaning agent PPA, and 50%-70% of matrix resin. The cleaning agent has the advantages of being able to quickly, forcefully and efficiently clean various adhesive substances on the surface of the barrel and screw, greatly improving the cleaning efficiency, but the disadvantages are also very obvious. A high proportion of glass fiber is used to forcefully remove stubborn residues through mechanical friction, which will cause irreversible damage to the screw.
[0007] There is an urgent need to develop a screw cleaning material that is environmentally friendly, has strong cleaning ability and does not cause damage to the screw. Summary of the invention
[0008] As described above, in order to solve the problems of easy agglomeration, uneven dispersion, insufficient cleaning power, and easy damage to the screw of the screw cleaning material, the purpose of the present invention is to provide a screw cleaning material that is environmentally friendly, has strong cleaning ability and does not cause damage to the screw, and its preparation method and application.
[0009] To this end, in a first aspect, the present invention provides a screw cleaning material, the raw materials of which include:
[0010]
[0011] The modified inorganic filler is an inorganic filler modified by an alcohol compound and a silane coupling agent.
[0012] In the screw cleaning material of the present invention, the modified inorganic filler is modified with an alcohol compound and a silane coupling agent, which can improve the dispersibility of the inorganic filler and the bonding force between the inorganic filler and the matrix resin. The present invention selects a matrix resin, a modified inorganic filler, a surfactant, a compatibilizer and an antioxidant for compounding, and the modified inorganic filler can be more evenly dispersed in the resin matrix. At the same time, through the physical friction and chemical action of each component, the dirt on the surface of the screw can be efficiently and thoroughly removed without causing damage to the screw.
[0013] In some preferred embodiments of the present invention, the modified inorganic filler is an inorganic filler modified by an alcohol compound and a silane coupling agent in sequence. In the screw cleaning material of the present invention, the modified inorganic filler is first dispersed by an alcohol compound, which not only serves as a solvent but also improves the dispersibility of the inorganic powder. The addition of a silane coupling agent can enhance the bonding force between the inorganic filler and the matrix resin. The two act synergistically, making the modification effect better than other dispersants.
[0014] In some embodiments of the present invention, the screw cleaning material does not contain glass fiber and strong alkaline reagents, such as sodium hydroxide and potassium hydroxide. Therefore, the screw cleaning material provided by the present invention has the advantages of being environmentally friendly and not easy to damage the screw.
[0015] In some embodiments of the present invention, the inorganic filler is selected from at least one of calcium carbonate, magnesium oxide and zinc oxide.
[0016] In some embodiments of the present invention, the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and vinyltriethoxysilane, preferably at least two.
[0017] In some embodiments of the present invention, the alcohol compound is selected from at least one of methanol, ethanol, ethylene glycol, propanol, and n-pentanol, and preferably selected from at least one of ethanol, ethylene glycol, propanol, and n-pentanol. The alcohol compound has a moderate volatilization rate, which can relatively reduce the agglomeration phenomenon between particles during the drying process, and is conducive to obtaining a mixed powder with good dispersibility.
[0018] In some embodiments of the present invention, in the raw material of the modified inorganic filler, the mass ratio of the inorganic filler to the alcohol compound is 1:6-8.
[0019] In some embodiments of the present invention, in the raw materials of the modified inorganic filler, the mass ratio of the inorganic filler to the silane coupling agent is 3-6:1.
[0020] In some embodiments of the present invention, the inorganic filler is calcium carbonate and zinc oxide, and the mass ratio of calcium carbonate to zinc oxide is 6-0.7:1, preferably 5-3:3. The present invention selects calcium carbonate and zinc oxide in a specific ratio as inorganic fillers, so that the screw cleaning material is not only less in amount and the cleaning time is reduced, but also the cleaning effect is significant.
[0021] In some embodiments of the present invention, the preparation method of the modified inorganic filler includes: immersing the inorganic filler in an alcohol compound for ultrasonic dispersion, filtering, and first drying to obtain an inorganic filler dispersion, spraying a silane coupling agent solution into the inorganic filler dispersion, stirring, and then performing a second drying.
[0022] The inorganic filler is immersed in an alcohol compound for ultrasonic dispersion, so that the inorganic filler is fully dispersed in ethanol, and then the silane coupling agent is sprayed to evenly cover the filler surface, which not only saves the amount of silane coupling agent, but also ensures the uniformity and stability of the modified inorganic filler modification effect, thereby improving the comprehensive performance of the material. In addition, compared with conventional modification methods such as simple mixing, the above-mentioned step-by-step modification method can more accurately control the modification process, improve the uniformity and stability of the modification effect, and thus improve the comprehensive performance of the material.
[0023] In some embodiments of the present invention, the conditions for ultrasonic dispersion include: under stirring, temperature 20-35° C., time 5-20 min, and ultrasonic power 100-500 watts.
[0024] In some embodiments of the present invention, the concentration of the silane coupling agent solution is 40-60 wt %.
[0025] In some embodiments of the present invention, the solvent of the silane coupling agent solution is selected from at least one of methanol, ethanol, ethylene glycol, propanol, and n-pentanol, preferably selected from at least one of ethanol, ethylene glycol, propanol, and n-pentanol.
[0026] In some embodiments of the present invention, the base resin is selected from at least one of polypropylene resin and polyethylene resin.
[0027] In some preferred embodiments of the present invention, the matrix resin is selected from at least one of polypropylene resins. The present invention uses polypropylene resin and modified inorganic filler as solid particles, which play a role of physical friction during the cleaning process and help to remove stubborn dirt on the surface of the screw. Under the action of the shear force of the screw, these particles can better adhere to the surface of the screw and remove dirt by friction. The modified inorganic filler has better compatibility with the matrix resin and can also take away impurities such as resin remaining on the screw. The particle surfaces of polypropylene and modified calcium carbonate have certain charges and functional groups, which can adsorb or chemically react with the dirt on the surface of the screw to further enhance the cleaning effect.
[0028] In some embodiments of the present invention, the surfactant is selected from at least one of polyoxyethylene lauryl ether phosphate salts, alkyl phosphates, dodecyl dimethyl benzyl ammonium chloride and alkylphenol polyoxyethylene ether.
[0029] In some embodiments of the present invention, the compatibilizer is selected from at least one of maleic anhydride grafted polypropylene.
[0030] In some embodiments of the present invention, the antioxidant is selected from pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris[2,4-di-tert-butylphenyl]phosphite, and the mass ratio between the two is 1:0.5-2.
[0031] In some embodiments of the present invention, the surfactant is selected from at least two of polyoxyethylene lauryl ether phosphate salts, alkyl phosphates, dodecyl dimethyl benzyl ammonium chloride and alkylphenol polyoxyethylene ether.
[0032] In some preferred embodiments of the present invention, the alkyl phosphate is a C8-C12 alkyl phosphate.
[0033] In some preferred embodiments of the present invention, the alkylphenol polyoxyethylene ether is a C8-C12 alkylphenol polyoxyethylene ether.
[0034] In some embodiments of the present invention, the surfactant is selected from dodecyl dimethyl benzyl ammonium chloride (DDBAC) and alkylphenol polyoxyethylene ether, and the mass ratio of the two is 1:0.5-2. The solid particles in the cleaning material, combined with DDBAC and alkylphenol polyoxyethylene ether, and with their excellent wetting and penetration properties, reduce the surface tension of the material, making it easier for the cleaning agent to penetrate into the tiny gaps on the surface of the screw, thereby improving the cleaning effect.
[0035] In some embodiments of the present invention, the base resin is selected from at least one copolymerized polypropylene resin, and the copolymerized polypropylene resin has a melt index of 2-10 g / 10 min at 230° C. and a load of 2.16 kg.
[0036] To this end, in a second aspect, the present invention provides a method for preparing the above-mentioned screw cleaning material, comprising the following steps: mixing the raw materials, melt extruding and strand granulating.
[0037] In some preferred embodiments of the present invention, the mixing conditions include: a rotation speed of 500-800 r / min and a time of 15-30 min.
[0038] In some preferred embodiments of the present invention, the conditions for melt extrusion include: the temperature of each zone of the screw extruder is 180±5℃ in zone 1, 190±5℃ in zone 2, 200±5℃ in zone 3, 205±5℃ in zone 4, 200±5℃ in zone 5, 190±5℃ in zone 6, 185±5℃ in zone 7, 190±5℃ in zone 8, 200±5℃ in zone 9, 205±5℃ in zone 10, 205±5℃ in die head, and the rotation speed is 400-500r / min.
[0039] To this end, in a third aspect, the present invention provides a method for cleaning a screw of a processing equipment, comprising the following steps: adding the above-mentioned screw cleaning material or the screw cleaning material obtained by the above-mentioned preparation method into the processing equipment for cleaning.
[0040] In some preferred embodiments of the present invention, the processing equipment is a screw extruder.
[0041] In some preferred embodiments of the present invention, the cleaning conditions include: the temperature of each zone of the screw extruder is: 190±5℃, zone two 200±5℃, zone three 210±5℃, zone four 215±5℃, zone five 210±5℃, zone six 200±5℃, zone seven 195±5℃, zone eight 200±5℃, zone nine 210±5℃, zone ten 215±5℃, die head 215±5℃, speed 400-500r / min, pressure 3-5MPa.
[0042] Cleaning conditions Under the above temperature conditions, some stubborn stains, such as carbonized polymers formed on the screw surface after high-temperature processing, are softened and melted, making them easier to be removed by the cleaning compound. In addition, under the above temperature conditions, the chemical reaction rate can be accelerated, for example, the chemical reaction between the active ingredients in the cleaning compound and the stains can be accelerated, thereby enhancing the cleaning efficiency.
[0043] In addition, the cleaning temperature is slightly higher than the temperature for preparing the cleaning material, which can reduce the viscosity of the cleaning material, enhance its fluidity, and allow the cleaning material to better penetrate into every corner, gap and complex structure of the screw, ensuring that there is no dead angle in the cleaning. In addition, the cleaning material provided by the present invention has good thermal stability, and increasing the cleaning temperature has no adverse effect on the cleaning material.
[0044] The cleaning conditions under the above pressure can, firstly, avoid physical damage to the screw caused by excessive pressure, such as deformation of the screw, which will affect the subsequent normal material conveying, plasticizing and mixing functions of the screw; secondly, avoid uneven spraying of the cleaning material caused by excessive pressure. Under the above pressure, the cleaning material can fully contact all surfaces of the screw, avoiding excessive force, causing the cleaning material to pass through certain channels too quickly, and not being able to fully stay on the entire screw surface and play a cleaning role, affecting the cleaning quality; thirdly, avoid splashing of the cleaning material caused by excessive pressure, causing pollution in the workplace, and wasting the cleaning material, increasing the cleaning cost.
[0045] The present invention has the following beneficial effects:
[0046] 1. In the screw cleaning material of the present invention, the modified inorganic filler is modified with alcohol compounds and silane coupling agents, which can improve the dispersibility of the inorganic filler and the bonding force between the inorganic filler and the matrix resin. The present invention selects the matrix resin, the modified inorganic filler and the surfactant, the compatibilizer and the antioxidant to compound, and the modified inorganic filler can be more evenly dispersed in the resin matrix. At the same time, through the physical friction and chemical action of each component, the dirt on the surface of the screw can be efficiently and thoroughly removed without causing damage to the screw.
[0047] 2. In the screw cleaning material of the present invention, polypropylene resin and modified inorganic filler are preferably used as solid particles, which play a role of physical friction during the cleaning process and help to remove stubborn dirt on the surface of the screw. Under the action of the shear force of the screw, these particles can better adhere to the surface of the screw and remove dirt by friction. The modified inorganic filler has better compatibility with the matrix resin and can also take away impurities such as resin remaining on the screw. The particle surfaces of polypropylene and modified calcium carbonate have certain charges and functional groups, which can adsorb or chemically react with the dirt on the surface of the screw to further enhance the cleaning effect.
[0048] 3. The present invention preferably uses calcium carbonate and zinc oxide in a specific ratio as inorganic fillers, so that the screw cleaning material not only has a small amount of use and reduces the cleaning time, but also has a significant cleaning effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 (a) and 1(b) are respectively the washed out materials after the extruder screw is washed out using the washing material prepared in Example 2.
[0050] Figure 1 (c) is the washing discharge after the washing of the extruder screw by the washing material prepared in Example 2 is completed.
[0051] Figure 1 (d) is the extrudate obtained after the cleaning of Example 2 is completed and the raw materials are added to the extruder again and the temperature is increased. DETAILED DESCRIPTION
[0052] The technical scheme of the present invention is further described below by specific embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0053] 1. Raw materials
[0054] The polypropylene resin PP is PP-2500HY (melt index is 2.2 g / 10 min at 230° C. and 2.16 kg load);
[0055] Nonylphenol polyoxyethylene ether was purchased from Sinopharm Wokai Reagent, CAS No.: 127087-87-0.
[0056] (II) Methods
[0057] The test method of melt index is based on GB / T-3682.
[0058] Example 1
[0059] Preparation of modified inorganic fillers
[0060] 25 g of calcium carbonate and 15 g of zinc oxide were weighed, immersed in 300 g of anhydrous ethanol, stirred at room temperature (25° C.) for 10 min under ultrasonic conditions, and then dried to obtain a dispersed mixed powder.
[0061] 10g of silane coupling agent KH-550 was dissolved in anhydrous ethanol to prepare a 50wt% solution, which was sprayed into the dispersed mixed powder, stirred for 30min, and dried to remove the anhydrous ethanol in the mixed powder to obtain a modified mixed powder.
[0062] Preparation of screw cleaning material
[0063] Raw materials: polypropylene resin PP, dodecyl dimethyl benzyl ammonium chloride, nonylphenol polyoxyethylene ether, maleic anhydride grafted PP, antioxidant 1010 and antioxidant 168. The specific dosage is shown in Table 1.
[0064] Add the above raw materials and modified mixed powder into a mixer, mix at a speed of 600 r / min for 30 min at room temperature of 25°C and in a dry environment, adjust the screw extruder parameters as follows: zone 1 180°C, zone 2 190°C, zone 3 200°C, zone 4 205°C, zone 5 200°C, zone 6 190°C, zone 7 185°C, zone 8 190°C, zone 9 200°C, zone 10 205°C, die head 205°C, speed 400 r / min, melt extrusion and strand granulation to obtain screw cleaning material.
[0065] Example 2
[0066] Preparation of modified inorganic fillers
[0067] 20 g of calcium carbonate and 15 g of zinc oxide were weighed, immersed in 250 g of anhydrous ethanol, stirred at room temperature (25° C.) for 10 min under ultrasonic conditions, and then dried to obtain a dispersed mixed powder.
[0068] 9g of silane coupling agent KH-550 was dissolved in anhydrous ethanol to prepare a 50wt% solution, which was sprayed into the dispersed mixed powder, stirred for 30min, and dried to remove the anhydrous ethanol in the mixed powder to obtain a modified mixed powder.
[0069] Preparation of screw cleaning material
[0070] Raw materials: polypropylene resin PP, dodecyl dimethyl benzyl ammonium chloride, nonylphenol polyoxyethylene ether, maleic anhydride grafted PP, antioxidant 1010 and antioxidant 168. The specific dosage is shown in Table 1.
[0071] Add the above raw materials and modified mixed powder into a mixer, mix at a speed of 600 r / min for 30 min at room temperature of 25°C and in a dry environment, adjust the screw extruder parameters as follows: zone 1 180°C, zone 2 190°C, zone 3 200°C, zone 4 205°C, zone 5 200°C, zone 6 190°C, zone 7 185°C, zone 8 190°C, zone 9 200°C, zone 10 205°C, die head 205°C, speed 400 r / min, melt extrusion and strand granulation to obtain screw cleaning material.
[0072] Example 3
[0073] Preparation of modified inorganic fillers
[0074] 15 g of calcium carbonate and 15 g of zinc oxide were weighed, immersed in 200 g of anhydrous ethanol, stirred at room temperature (25° C.) for 10 min under ultrasonic conditions, and then dried to obtain a dispersed mixed powder.
[0075] 8g of silane coupling agent KH-550 was dissolved in anhydrous ethanol to prepare a 50wt% solution, which was sprayed into the dispersed mixed powder, stirred for 30 minutes, and dried to remove the anhydrous ethanol in the mixed powder to obtain a modified mixed powder.
[0076] Preparation of screw cleaning material
[0077] Raw materials: polypropylene resin PP, dodecyl dimethyl benzyl ammonium chloride, nonylphenol polyoxyethylene ether, maleic anhydride grafted PP, antioxidant 1010 and antioxidant 168. The specific dosage is shown in Table 1.
[0078] Add the above raw materials and modified mixed powder into a mixer, mix at a speed of 600 r / min for 30 min at room temperature of 25°C and in a dry environment, adjust the screw extruder parameters as follows: zone 1 180°C, zone 2 190°C, zone 3 200°C, zone 4 205°C, zone 5 200°C, zone 6 190°C, zone 7 185°C, zone 8 190°C, zone 9 200°C, zone 10 205°C, die head 205°C, speed 400 r / min, melt extrusion and strand granulation to obtain screw cleaning material.
[0079] Example 4
[0080] Preparation of modified inorganic fillers
[0081] 25 g of calcium carbonate and 10 g of zinc oxide were weighed, immersed in 250 g of anhydrous ethanol, stirred at room temperature (25° C.) for 10 min under ultrasonic conditions, and then dried to obtain a dispersed mixed powder.
[0082] 9g of silane coupling agent KH-550 was dissolved in anhydrous ethanol to prepare a 50wt% solution, which was sprayed into the dispersed mixed powder, stirred for 30min, and dried to remove the anhydrous ethanol in the mixed powder to obtain a modified mixed powder.
[0083] Preparation of screw cleaning material
[0084] Raw materials: polypropylene resin PP, dodecyl dimethyl benzyl ammonium chloride, nonylphenol polyoxyethylene ether, maleic anhydride grafted PP, antioxidant 1010 and antioxidant 168. The specific dosage is shown in Table 1.
[0085] Add the above raw materials and modified mixed powder into a mixer, mix at a speed of 600 r / min for 30 min at room temperature of 25°C and in a dry environment, adjust the screw extruder parameters as follows: zone 1 180°C, zone 2 190°C, zone 3 200°C, zone 4 205°C, zone 5 200°C, zone 6 190°C, zone 7 185°C, zone 8 190°C, zone 9 200°C, zone 10 205°C, die head 205°C, speed 400 r / min, melt extrusion and strand granulation to obtain screw cleaning material.
[0086] Example 5
[0087] Preparation of modified inorganic fillers
[0088] 30 g of calcium carbonate and 5 g of zinc oxide were weighed, immersed in 250 g of anhydrous ethanol, stirred at room temperature (25° C.) for 10 min under ultrasonic conditions, and then dried to obtain a dispersed mixed powder.
[0089] 9g of silane coupling agent KH-550 was dissolved in anhydrous ethanol to prepare a 50wt% solution, which was sprayed into the dispersed mixed powder, stirred for 30min, and dried to remove the anhydrous ethanol in the mixed powder to obtain a modified mixed powder.
[0090] Preparation of screw cleaning material
[0091] Raw materials: polypropylene resin PP, dodecyl dimethyl benzyl ammonium chloride, nonylphenol polyoxyethylene ether, maleic anhydride grafted PP, antioxidant 1010 and antioxidant 168. The specific dosage is shown in Table 1.
[0092] Add the above raw materials and modified mixed powder into a mixer, mix at a speed of 600 r / min for 30 min at room temperature of 25°C and in a dry environment, adjust the screw extruder parameters as follows: zone 1 180°C, zone 2 190°C, zone 3 200°C, zone 4 205°C, zone 5 200°C, zone 6 190°C, zone 7 185°C, zone 8 190°C, zone 9 200°C, zone 10 205°C, die head 205°C, speed 400 r / min, melt extrusion and strand granulation to obtain screw cleaning material.
[0093] Example 6
[0094] Preparation of modified inorganic fillers
[0095] 15 g of calcium carbonate and 20 g of zinc oxide were weighed, immersed in 250 g of anhydrous ethanol, stirred at room temperature (25° C.) for 10 min under ultrasonic conditions, and then dried to obtain a dispersed mixed powder.
[0096] 9g of silane coupling agent KH-550 was dissolved in anhydrous ethanol to prepare a 50wt% solution, which was sprayed into the dispersed mixed powder, stirred for 30min, and dried to remove the anhydrous ethanol in the mixed powder to obtain a modified mixed powder.
[0097] Preparation of screw cleaning material
[0098] Raw materials: polypropylene resin PP, dodecyl dimethyl benzyl ammonium chloride, nonylphenol polyoxyethylene ether, maleic anhydride grafted PP, antioxidant 1010 and antioxidant 168. The specific dosage is shown in Table 1.
[0099] Add the above raw materials and modified mixed powder into a mixer, mix at a speed of 600 r / min for 30 min at room temperature of 25°C and in a dry environment, adjust the screw extruder parameters as follows: zone 1 180°C, zone 2 190°C, zone 3 200°C, zone 4 205°C, zone 5 200°C, zone 6 190°C, zone 7 185°C, zone 8 190°C, zone 9 200°C, zone 10 205°C, die head 205°C, speed 400 r / min, melt extrusion and strand granulation to obtain screw cleaning material.
[0100] Example 7
[0101] Preparation of modified inorganic fillers
[0102] 24 g of calcium carbonate and 12 g of zinc oxide were weighed, immersed in 250 g of anhydrous ethanol, stirred at room temperature (25° C.) for 10 min under ultrasonic conditions, and then dried to obtain a dispersed mixed powder.
[0103] 10g of silane coupling agent KH-550 was dissolved in anhydrous ethanol to prepare a 50wt% solution, which was sprayed into the dispersed mixed powder, stirred for 30min, and dried to remove the anhydrous ethanol in the mixed powder to obtain a modified mixed powder.
[0104] Preparation of screw cleaning material
[0105] Raw materials: polypropylene resin PP, dodecyl dimethyl benzyl ammonium chloride, nonylphenol polyoxyethylene ether, maleic anhydride grafted PP, antioxidant 1010 and antioxidant 168. The specific dosage is shown in Table 1.
[0106] Add the above raw materials and modified mixed powder into a mixer, mix at a speed of 600 r / min for 30 min at room temperature of 25°C and in a dry environment, adjust the screw extruder parameters as follows: zone 1 180°C, zone 2 190°C, zone 3 200°C, zone 4 205°C, zone 5 200°C, zone 6 190°C, zone 7 185°C, zone 8 190°C, zone 9 200°C, zone 10 205°C, die head 205°C, speed 400 r / min, melt extrusion and strand granulation to obtain screw cleaning material.
[0107] Example 8
[0108] The difference from Example 2 is that the polypropylene resin PP-2500HY is replaced by the polyethylene resin PE-2420H (melt index is 0.9 g / 10 min at 190° C. and a load of 2.16 kg).
[0109] Example 9
[0110] The difference from Example 2 is that zinc oxide is replaced by magnesium oxide.
[0111] Example 10
[0112] The difference from Example 2 is that zinc oxide is replaced by calcium carbonate.
[0113] Embodiment 11
[0114] The difference from Example 2 is that calcium carbonate is replaced by zinc oxide.
[0115] Example 12
[0116] The difference from Example 2 is that the mass of KH-550 is replaced from 9 g to 3 g.
[0117] Embodiment 13
[0118] The difference from Example 2 is that dodecyl dimethyl benzyl ammonium chloride is replaced by nonylphenol polyoxyethylene ether.
[0119] Embodiment 14
[0120] The difference from Example 2 is that nonylphenol polyoxyethylene ether is replaced by dodecyl dimethyl benzyl ammonium chloride.
[0121] Comparative Example 1
[0122] Preparation of screw cleaning material
[0123] Raw materials: polypropylene resin PP, calcium carbonate, vinyl bisstearamide EBS, antioxidant 1010 and antioxidant 168. The specific dosage is shown in Table 1.
[0124] Add the above raw materials into a mixer, mix them thoroughly at a speed of 600r / min under room temperature of 25°C and dry environment, adjust the parameters of the screw extruder to: zone 1 180°C, zone 2 190°C, zone 3 200°C, zone 4 205°C, zone 5 200°C, zone 6 190°C, zone 7 185°C, zone 8 190°C, zone 9 200°C, zone 10 205°C, die head 205°C, speed of 400r / min, melt extrusion and strand granulation to obtain the screw cleaning material.
[0125] Comparative Example 2
[0126] Preparation of modified inorganic fillers
[0127] Weigh 20g of calcium carbonate and 15g of zinc oxide, mix them evenly to obtain a mixed powder. Dissolve 9g of silane coupling agent KH-550 in anhydrous ethanol to prepare a 50wt% solution, spray it into the mixed powder, stir at room temperature (25°C) for 30min, and dry to remove the anhydrous ethanol in the mixed powder to obtain a modified mixed powder.
[0128] The screw cleaning material was prepared in the same manner as in Example 1.
[0129] Comparative Example 3
[0130] Preparation of inorganic fillers
[0131] 20 g of calcium carbonate and 15 g of zinc oxide were weighed, immersed in 250 g of anhydrous ethanol, stirred at room temperature (25° C.) for 10 min under ultrasonic conditions, and then dried to obtain a dispersed mixed powder.
[0132] The screw cleaning material was prepared in the same manner as in Example 1.
[0133] Comparative Example 4
[0134] Preparation of modified inorganic fillers
[0135] 20 g of calcium carbonate and 15 g of zinc oxide were weighed, immersed in an aqueous solution of desugared condensed sodium lignin sulfonate with a concentration of 0.8 wt%, stirred at room temperature (25° C.) for 10 min under ultrasonic conditions, and then dried to obtain a dispersed mixed powder.
[0136] 9g of silane coupling agent KH-550 was dissolved in anhydrous ethanol to prepare a 50wt% solution, which was sprayed into the dispersed mixed powder, stirred for 30min, and dried to remove the anhydrous ethanol in the mixed powder to obtain a modified mixed powder.
[0137] The screw cleaning material was prepared in the same manner as in Example 2.
[0138] Comparative Example 5
[0139] Preparation of modified inorganic fillers
[0140] 20 g of calcium carbonate and 15 g of zinc oxide were weighed, immersed in an aqueous solution of desugared condensed sodium lignin sulfonate with a concentration of 0.8 wt%, stirred at room temperature (25° C.) for 10 min under ultrasonic conditions, and then dried to obtain a dispersed mixed powder.
[0141] 9g of silane coupling agent KH-550 was dissolved in water to prepare a 50wt% solution, which was sprayed into the dispersed mixed powder, stirred for 30 minutes, and dried to remove anhydrous ethanol in the mixed powder to obtain a modified mixed powder.
[0142] The screw cleaning material was prepared in the same manner as in Example 2.
[0143] Table 1
[0144]
[0145]
[0146] Test Example 1
[0147] The twin-screw extruder was cleaned using the screw cleaning materials prepared in the above embodiments and comparative examples.
[0148] The twin-screw extruder is used to switch the black acrylonitrile-butadiene-styrene copolymer ABS to transparent polycarbonate PC. Taking the cleaning of ABS black as an example, the above-mentioned screw cleaning material is added to the twin-screw extruder. The temperature of each zone of the twin-screw extruder is: 200℃ in zone 1, 210℃ in zone 2, 220℃ in zone 3, 230℃ in zone 4, 240℃ in zone 5, 240℃ in zone 6, 230℃ in zone 7, 220℃ in zone 8, 210℃ in zone 9, 215℃ in zone 10, 210℃ in die head, 400r / min speed, 3-5MPa pressure. Cleaning is carried out continuously until the extrudate meets the color of the extruded rubber block and the raw material, and there are no color streaks or black spots, that is, until the screw is cleaned, and finally the amount of cleaning material and the time consumed are recorded. The test results are shown in Table 2.
[0149] Table 2
[0150]
[0151]
[0152] As can be seen from Table 1-2, the screw cleaning material prepared in Example 1-14 has a significant cleaning effect. In particular, Example 1-7 uses a specific ratio of calcium carbonate and zinc oxide as inorganic fillers, so that the final product achieves a unique balance and synergistic effect in performance, and the cleaning effect is significant. That is to say, under the action of the shear force of the screw, the powder mixture of this ratio can be better attached to the surface of the screw after modification, and the dirt can be removed by friction. The modified calcium carbonate and zinc oxide have better compatibility with the matrix resin, and can also take away impurities such as resin remaining on the screw. The effect is much better than using a single calcium carbonate as a filler, which can save at least 38% of cleaning time and 50% of cleaning materials; at most 75% of cleaning time and 65% of cleaning materials.
[0153] Compared with Examples 9-11, Example 2 uses calcium carbonate and zinc oxide in a specific ratio as inorganic fillers, which significantly reduces the amount of cleaning material used and saves cleaning time.
[0154] Compared with Example 2, Comparative Examples 2 and 3 have different modification methods for the inorganic fillers. The amount of cleaning material used is 20kg and 25kg more than that of Example 2, respectively, and the cleaning time is 30min and 35min longer, respectively. That is, the cleaning effect of adding the modified inorganic filler prepared by the present invention to replace the ordinary inorganic filler is significantly better.
[0155] Compared with Example 2, Comparative Examples 4 and 5 use desugared condensed sodium lignin sulfonate instead of ethanol. Although desugared condensed sodium lignin sulfonate can be used as a dispersant, the cleaning effects of Comparative Examples 4 and 5 are significantly worse, that is, the cleaning material prepared by the present invention has significantly better effect.
[0156] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A screw cleaning material, characterized in that: The raw materials of the screw cleaning material include, by weight: The modified inorganic filler is an inorganic filler modified by an alcohol compound and a silane coupling agent.
2. The screw cleaning material according to claim 1, characterized in that: The inorganic filler is selected from at least one of calcium carbonate, magnesium oxide and zinc oxide; and / or The silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and vinyltriethoxysilane; and / or The alcohol compound is selected from at least one of methanol, ethanol, ethylene glycol, propanol and n-pentanol; and / or In the raw materials of the modified inorganic filler, the mass ratio of the inorganic filler to the alcohol compound is 1:6-8; and / or In the raw materials of the modified inorganic filler, the mass ratio of the inorganic filler to the silane coupling agent is 3-6:
1.
3. The screw cleaning material according to claim 2, characterized in that: The inorganic filler is calcium carbonate and zinc oxide, and the mass ratio of the calcium carbonate to the zinc oxide is 6-0.7:
1.
4. The screw cleaning material according to any one of claims 1 to 3, characterized in that: The preparation method of the modified inorganic filler comprises: immersing the inorganic filler in an alcohol compound, performing ultrasonic dispersion, filtering, and first drying to obtain an inorganic filler dispersion, spraying a silane coupling agent solution into the inorganic filler dispersion, stirring, and then performing a second drying.
5. The screw cleaning material according to claim 4, characterized in that: The conditions of ultrasonic dispersion include: under stirring, temperature 20-35° C., time 5-20 min, ultrasonic power 100-500 watts; and / or The concentration of the silane coupling agent solution is 40-60wt%; and / or The solvent of the silane coupling agent solution is selected from at least one of methanol, ethanol, ethylene glycol, propanol and n-pentanol.
6. The screw cleaning material according to any one of claims 1 to 3, characterized in that: The base resin is selected from at least one of polypropylene resin and polyethylene resin; and / or The surfactant is selected from at least one of polyoxyethylene lauryl ether phosphate salts, alkyl phosphates, dodecyl dimethyl benzyl ammonium chloride and alkylphenol polyoxyethylene ether; and / or The compatibilizer is selected from at least one of maleic anhydride grafted polypropylene; and / or The antioxidant is selected from pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] and tris[2,4-di-tert-butylphenyl] phosphite, and the mass ratio of the two is 1:0.5-2.
7. The screw cleaning material according to claim 6, characterized in that: The matrix resin is selected from at least one copolymerized polypropylene resin, and the copolymerized polypropylene resin has a melt index of 2-10 g / 10 min at 230° C. and a load of 2.16 kg.
8. The screw cleaning material according to claim 6, characterized in that: The surfactant is selected from at least two of polyoxyethylene lauryl ether phosphate salts, alkyl phosphates, dodecyl dimethyl benzyl ammonium chloride and alkylphenol polyoxyethylene ether.
9. The method for preparing the screw cleaning material according to any one of claims 1 to 8, characterized in that: The following steps are involved: After the raw materials are mixed, they are melt extruded and pelletized.
10. A method for cleaning a screw of a processing equipment, characterized in that: The method comprises the following steps: adding the screw cleaning material described in any one of claims 1 to 8 or the screw cleaning material prepared by the preparation method described in claim 9 into processing equipment for cleaning.
Citation Information
Patent Citations
Efficient plastic screw cleaning agent, production method and use method
CN105924931A
Cleaning agent for screw rod of plastic extruding machine or injection molding machine
CN106674723A
Preparation method for calcium carbonate for screw cleaning agent
CN106978277A
Solid energy saving screw cleaning agent
CN101838420A
Double-screw high-efficiency environment-friendly pelletized particle cleaning agent and production method thereof
CN102618401A